Aesthetics and functions of craft art in public art space (Harmonia: Journal of Arts Research and Education, 2017)
The problem in this research is about how to assess the aesthetics and functions of craft art in Indonesian city public space compare to other cities in other countries. It is also about how these craft arts can be used to improve the aesthetics and strength a city’s identity. Approaches used in this research are aesthetic theory and sociology of art. Aesthetic theory is used to assess the craft art textually or intra aesthetics. Sociology of art theory is used to see how craft art role can fulfil its function as a medium for craftsperson to participate in creating an art work that is useful to the society, so the existence of craft art in public space can give positive impacts towards the urban society. Results of this research is a positive impact of the craft art existence in some Indonesian public places where craft art becomes a city icon or identity with a special symbol attached to it; as a sign of historical or contemporary works. It also creates the aesthetics of a city design to be more humanist and healthy for all citizens.